Composite material consisting of microporous β-TCP ceramic and alginate for delayed release of antibiotics. (15th March 2017) - Seidenstuecker, Michael; Ruehe, Juergen; Suedkamp, Norbert P.; Serr, Annerose; Wittmer, Annette; Bohner, Marc; Bernstein, Anke; Mayr, Hermann O.
Graphical abstract: Abstract: Objective: The aim of this study was to produce a novel composite of microporous β-TCP filled with alginate and Vancomycin (VAN) to prolong the release behavior of the antibiotic for up to 28 days. Material and methods: Using the flow chamber developed by the group, porous ceramics in a directional flow were filled with alginates of different composition containing 50 mg/mL of antibiotics. After cross-linking the alginate with calcium ions, incubation took place in 10 mL double-distilled water for 4 weeks at 37 °C. At defined times (1, 2, 3, 6, 9, 14, 20 and 28 days), the liquid was completely exchanged and analyzed by capillary zone electrophoresis and microtiter trials. For statistical purposes, the mean and standard deviation were calculated and analyzed by ANOVA. Results: The release of VAN from alginate was carried out via an external calcium source over the entire period with concentrations above the minimal inhibitory concentration (MIC). The burst release measured 35.2 ± 1.5%. The release of VAN from alginate with an internal calcium source could only be observed over 14 days. The burst release here was 61.9 ± 4.3%. The native alginate's burst release was 54.1 ± 7.8%; that of the sterile alginate 40.5 ± 6.4%. The microtiter experiments revealed efficacy over the entire study period for VAN. The MIC value was determined in the release experiments as well in a range of 0.5–2.0 μg/mL against Staphylococcus aureus . Statement of Significance: Drug release systems based on β-TCP and hydrogels are well documented in literature. However, in all described systems the ceramic, as granule or powder, is inserted into a hydrogel. In our work, we do the opposite, a hydrogel which acts as reservoir for antibiotics is placed into a porous biodegradable ceramic. Eventually, this system should be applied as treatment of bone infections. Contrary to the "granule in hydrogel" composites it has the advantage of mechanical stability. Thus, it can take over functions of the bone during the healing process. For a quicker translation from our scientific research into clinical use, only FDA approved materials were used in this work.